Possibilities for developing reactive abilities of young judokas - Gorskaya, I. Y.; Medvedeva, L.E.; Kladov, E.V. (Modern Issues of Biomedicine, 2022)
The purpose of the study is to develop and test a methodology for developing reactive abilities of young judokas and determine the quantitative range of the possibility of developing these abilities in the age range of 8-9 years under the influence of accentuated training. The article gives a brief description of the content of the developed methodology, its components, means of developing reactive abilities for beginner judokas, and discloses the algorithm for implementing the methodology in the training process. The results of experimental testing have been noted. We have conducted an analysis of growth rates of various indicators of reactive abilities under the accentuated impact.